RECOVERING METHOD FOR THERMOPLASTIC RESIN WITH COATING FILM, REINFORCING MATERIAL (2) - ITO FUMISAKU; OKAMOTO HIDEMASA (1995)
PURPOSE:To recover a resin component of high purity and reinforcing material by forming solid of specific water content value containing a thermoplastic resin with coating film and/or reinforcing material, carboxylate coupled to a polymer chain and water, and applying water to the solid to fine particles as aqueous dispersing material having characteristics dispersing in water state. CONSTITUTION:The method for recovering thermoplastic resin with coating film, reinforcing material comprises the steps of modifying the resin with the film and/or the material having carboxylate coupled to a polymer chain by melting and kneading, then applying water during the melting and kneading to neutralize the modified material, and forming the solid content to aqueous dispersing material having characteristics uniformly dispersing in water state as fine particles by using a twin-screw extruder having a plurality of vent ports. The dispersing material is apparently solid having a water content of 3-25wt.%. The dispersing material is thrown in water or hot water, and agitated to afford an emulsified material. The emulsified material is separated to resin content, coating film and/or reinforcing material by precipitating, centrifugal separation, filtering, etc.